As tarjas de arco cruzeiro das paróquias mineiras setecentistas: forma e significado - João Henrique Grossi Sad Júnior (2018)
This dissertation deals with the ornamental piece known as targe, specifically the one which decorated the top of crossing arches at parochial churches in Minas Gerais in the 18th century. The research inquires into historical, iconographical, functional and aesthetical aspects related to those targes. The text presents a historical overview of religious architecture’s heraldry, since the appearance of its prototype – the ancient imagines clipeatae (shielded images) –, all the way through to the targes of 18th century religious architecture in Portugal and Minas Gerais. Stylistic aspects of Baroque and Rococo in Minas are presented, as well as those entities who ordered the making of sacred ornamentation – the portuguese monarchy, the colonial Catholic Church and mineiro brotherhoods – to whom the emblems on top of the crossing arches referred to. Finally, there are a number of detailed analyses of distinguished mineiro targes, including the meaning of their symbols.